2018
DOI: 10.1038/s41598-018-29786-9
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α increases the intrinsic excitability of cerebellar Purkinje cells through elevating glutamate release in Bergmann Glia

Abstract: For decades, the glial function has been highlighted not only as the ‘structural glue’, but also as an ‘active participant’ in neural circuits. Here, we suggest that tumor necrosis factor α (TNF-α), a key inflammatory cytokine, alters the neural activity of the cerebellar Purkinje cells (PCs) by facilitating gliotransmission in the juvenile male rat cerebellum. A bath application of TNF-α (100 ng/ml) in acute cerebellar slices elevates spiking activity of PCs with no alterations in the regularity of PC firings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…In this study, we used a low dose of TNF-α, which is slightly higher than physiological concentrations [72] but far below those concentrations that can cause neuronal toxicity [7578], and found that TNF-α demonstrated a range of effects on the membrane properties of hippocampal CA1 neurons. The increased neuronal excitability induced by TNF-α treatment is in line with previous findings in rat cerebellar Purkinje cells [79], cultured cortical neurons [80], dorsal root ganglion [81, 82], rat suprachiasmatic nuclear neurons [83], neurons from rat subfornical organ [84], and in excised guinea pig spinal cord tissue [78]. This increased excitability may be attributed to the changes in neuronal membrane properties [83], including an increase in calcium current observed in cultured rat hippocampal neurons [85] and cultured sympathetic neurons from neonatal rat superior cervical ganglia [86], in transient outward potassium currents in cultured cortical neurons from embryonic rats [75], in sodium current observed in cultured mouse cortical neurons [80] and isolated rat dorsal root ganglion [81], or the suppression of sustained potassium currents in rat small dorsal root ganglion neurons [87].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we used a low dose of TNF-α, which is slightly higher than physiological concentrations [72] but far below those concentrations that can cause neuronal toxicity [7578], and found that TNF-α demonstrated a range of effects on the membrane properties of hippocampal CA1 neurons. The increased neuronal excitability induced by TNF-α treatment is in line with previous findings in rat cerebellar Purkinje cells [79], cultured cortical neurons [80], dorsal root ganglion [81, 82], rat suprachiasmatic nuclear neurons [83], neurons from rat subfornical organ [84], and in excised guinea pig spinal cord tissue [78]. This increased excitability may be attributed to the changes in neuronal membrane properties [83], including an increase in calcium current observed in cultured rat hippocampal neurons [85] and cultured sympathetic neurons from neonatal rat superior cervical ganglia [86], in transient outward potassium currents in cultured cortical neurons from embryonic rats [75], in sodium current observed in cultured mouse cortical neurons [80] and isolated rat dorsal root ganglion [81], or the suppression of sustained potassium currents in rat small dorsal root ganglion neurons [87].…”
Section: Discussionsupporting
confidence: 91%
“…This plasticity resembles the previously reported Ihdownregulation-dependent IP in PCs [47]. While both Yamamoto et al [126] and Shim et al [173] showed that exposure to TNF-a increased the firing frequency of PCs, Shim et al [173] have investigated PC excitability following 1-h of incubation with TNF-a. The time spam would possibly provoke another downstream cascade after the activation of TNF receptors or boosting cytokine releases.…”
Section: Immunity-induced Neuronal Excitability Plasticity and Behavisupporting
confidence: 83%
“…Related behavioral phenotypes had been observed in other groups [171,172], suggesting the control of animals' mood or sociability by cerebellar anterior lobes (paleocerebellum, i.e., old or ancient cerebellum, Berntson & Torello [36]) and related regions receiving their neural projection. On the other hand, Shim et al [173] have reported an increase in PC excitability via Bergman glial activity, which was accompanied by a decrease in Ih current. This plasticity resembles the previously reported Ihdownregulation-dependent IP in PCs [47].…”
Section: Immunity-induced Neuronal Excitability Plasticity and Behavimentioning
confidence: 96%
See 1 more Smart Citation
“…IgG further possesses pro-inflammatory properties, promoting microglia recruitment and upregulation of inflammatory cytokines [124,141,142]. Some of the other chemokines found to be elevated in ALS-CSF include IL-6, TNF-α and TGF-β [81,130,172], with the finding of raised TNF-α levels being particularly interesting, given its associations with glutamate excitotoxicity [43,178,218]. Whilst their direct involvement in ALS pathophysiology is still unknown, the presence of these different immune factors in ALS-CSF, some of which have been shown to be neurotoxic, could suggest an important role for CSF in neuroinflammation, with the neurotoxic environment possibly favoured by altered CSF dynamics and reduced clearance.…”
Section: Neuroinflammationmentioning
confidence: 99%